Digital Forensic Science - Suresh Kumar Shetty, B; Shetty H, Pavanchand (IntechOpen, 2020)
It is our pleasure to place before you the book Digital Forensic Science. This book makes up a major part of the broad specialty of Digital Forensic Science, comprising mainly of tools and technologies of cyber forensic experts for their future practice. This book has been designed to merge a range of new ideas and unique works of authors from topics like fundamental principles of forensic cyber analysis, and protocols and rules needed for the best digital forensics. We hope that it will be useful to practitioners of forensic medicine, experts, cyber experts, law makers, investigating authorities, and undergraduate and postgraduate medical school graduates of medicine.